Strengthening health systems in Africa: a case study of the Kenya field epidemiology training program for local frontline health workers - Zeinab Gura Roka; Jane Githuku; Mark Obonyo; Waqo Boru; Tura Galgalo; Samuel Amwayi; Jackson Kioko; David Njoroge; James Anthony Ransom (Frontiers Media S.A., 2017)
Abstract The logistical and operational challenges to improve public health practice capacity across Africa are well documented. This report describes Kenya's Field Epidemiology and Laboratory Training Program's (KFELTP) experience in implementing frontline public health worker training to transfer knowledge and practical skills that help strengthen their abilities to detect, document, respond to, and report unusual health events. Between May 2014 and May 2015, KFELTP hosted five training courses across the country to address practice gaps among local public health workers. Participants completed a 10-week process: two 1-week didactic courses, a 7-week field project, and a final 1-week course to present and defend the findings of their field project. The first year was a pilot period to determine whether the program could fit into the existing 2-year KFELTP model and whether this frontline-level training would have an impact on local practice. At the end of the first year, KFELTP certified 167 frontline health workers in field epidemiology and data management. This paper concludes that local, national, and international partnerships are critical for improving local public health response capacity and workforce development training in an African setting.